CANONICAL RELATIONS MORPHOLOGIC FEATURES, MOTOR ABILITIES AND TESTS WITH SITACIONI BASKETBALL PLAYERS AGED 12-14 YEARS - Zulfo Aruković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The aim of this istraživanjua is identifying the canonical correlation between two multidimensional space, the space of morphological characteristics and basic mo¬tor skills room, basketball od12 to 14 years of success on the result of situ¬atio¬nal-motor tests of basketball games. The study was conducted on a sample of 70 players.